The Effect of Infrastructure on Economic Growth in Regencies and Cities in Special Region of Yogyakarta Province - Anisa Nurpita; Rifki Khoirudin (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2023)
This study employed panel data regression to estimate the variables. The estimation revealed three results. First, the average economic growth in the Special Region of Yogyakarta Province in 2009-2019 is 5.30 percent. Second, most public schools are in Gunungkidul Regency, and the least number of private schools are in Yogyakarta City. Then, the highest numbers of public hospitals are in Sleman Regency, and the least is in Gunungkidul Regency. The highest numbers of public health centers are in Gunungkidul Regency, and the least is in Yogyakarta City. Third, the partial test results revealed that three independent variables have a significant effect on the dependent variable. The number of public schools has a negatively significant effect on economic growth. The number of private schools has a negatively significant effect on economic growth.